answersLogoWhite

0


Best Answer

square root (y) / Square root (3)

root (y) / 1.73

User Avatar

Wiki User

โˆ™ 2010-11-04 22:41:14
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.74
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
834 Reviews

Add your answer:

Earn +20 pts
Q: What is the square root of y over 3?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

What is the physical meaning of a square root?

A square root is taking a number X and determining which two same numbers times each other, or Y*Y equal X. If X equals 9, the square root of it is 3; that is 3 (Y) multiplied by 3 (Y) is 9.


What is 2 square root x - 3 square root y over square root x plus square root y?

5


What are two numbers whose sum -6 and product is -5?

-2 and -3Check:(-2) + (-3) = -5(-2)(-3) = 6Thus -2 and -3 are not the required numbers. let's find them: x + y = -6xy = -5 y = -x -6x(-x - 6) = -5-x^2 - 6x = -5x^2 + 6x = 5x^2 + 6x + 9 = 5 + 9(x + 3)^2 = 14x + 3 = (+ & -)square root of 14x = -3 (+ & -)square root of 14x = -3 + square root of 14 or x = - 3 - square root of 14y = -x - 6y = 3 - square root of 14 - 6 or y = 3 + square root of 14 - 6y = -3 - square root of 14 or y = -3 + square root of 14Check:(-3 + square root of 14) + (-3 - square root of 14) = -6(-3 + square root of 14)(-3 - square root of 14) = -5 ?(-3)^2 - (square root of 14)^2 = -5 ?9 - 14 = -5Check also tow other numbers.


Square root 9x2 y6?

3x y^3


What is the square root of x - y divided by square root of x y?

x=y


The difference between square and square roots?

If X is the square of Y then Y is a square root of X. But, -Y is also a square root.


What is the square root of root x plus 3 times the square root of x?

y = sqrt X + 3sqrt X is the same as y = 4 sqrt X


Log of square root of y?

log of the square root of 'y' = 1/2 sqrt(y)


What is the square root of y to the 11th power mutiplied by the square root of y?

y6


What is the square root of 25X to the second power y?

5x times the square root of y


How do you simplify the radical?

One step you usually want to take is to move any perfect square out of the radical. Example 1, with numbers: root(12) = root(4x3) = root(4) x root(3) = 2 root(3) Example 2, with variables: root(y cubed) = root(y squared times y) = root(y squared) times root(y) = y root(y)


Find the two numbers whose product is 1 and whose sum is 1?

x + y = 1xy = 1y = 1 - xx(1 - x) = 1x - x^2 = 1-x^2 + x - 1 = 0 or multiplying all terms by -1;(-x^2)(-1) + (x)(-1) - (1)(-1) = 0x^2 - x + 1 = 0The roots are complex numbers. Use the quadratic formula and find them:a = 1, b = -1, and c = 1x = [-b + square root of (b^2 - (4)(a)(c)]/2a orx = [-b - square root of (b^2 - (4)(a)(c)]/2aSox = [-(-1) + square root of ((-1)^2 - (4)(1)(1)]/2(1)x = [1 + square root of (1 - 4]/2x = [1 + square root of (- 3)]/2 orx = [1 + square root of (-1 )(3)]/2; substitute (-1) = i^2;x = [1 + square root of (i^2 )(3)]/2x = [1 + (square root of 3)i]/2x = 1/2 + [i(square root of 3]/2 andx = 1/2 - [i(square root of 3)]/2Since we have two values for x, we will find also two values for yy = 1 - xy = 1 - [1/2 + (i(square root of 3))/2]y = 1 - 1/2 - [i(square root of 3)]/2y = 1/2 - [i(square root of 3)]/2 andy = 1 - [1/2 - (i(square root of 3))/2)]y = 1 - 1/2 + [i(square root of 3))/2]y = 1/2 + [i(square root of 3)]/2Thus, these numbers are:1. x = 1/2 + [i(square root of 3)]/2 and y = 1/2 - [i(square root of 3)]/22. x = 1/2 - [i(square root of 3)]/2 and y = 1/2 + [i(square root of 3)]/2Let's check this:x + y = 11/2 + [i(square root of 3)]/2 +1/2 - [i(square root of 3)]/2 = 1/2 + 1/2 = 1xy = 1[1/2 + [i(square root of 3)]/2] [1/2 - [i(square root of 3)]/2]= (1/2)(1/2) -(1/2)[i(square root of 3)]/2] + [i(square root of 3)]/2](1/2) - [i(square root of 3)]/2] [i(square root of 3)]/2]= 1/4 - [i(square root of 3)]/4 + [i(square root of 3)]/4 - (3i^2)/4; substitute ( i^2)=-1:= 1/4 - [(3)(-1)]/4= 1/4 + 3/4= 4/4=1In the same way we check and two other values of x and y.

People also asked